Effect of peak-to-peak amplitude at the base of crimped spiral fins on the air-side performance of crimped spiral fin-and-tube heat exchangers - Thawatchai Keawkamrop; Somchai Wongwises (Applications in Engineering Science)
This experimental study investigates the effect of peak-to-peak amplitude (PTPA) at the base of a crimped spiral fin (CSF) on the air-side performance of a crimped spiral fin-and-tube heat exchanger (CSFTHX) within a 3,000 to 14,000 Reynolds number range. Both plain spiral fins (PSFs) and CSFs are examined. The PTPA is the main geometric parameter of interest in this study. We investigated CSFTHXs with a 19.05 mm outer tube diameter, a fin density of 5 fins per inch (equivalent to a fin pitch of 5.08 mm). The selected peak-to-peak amplitude (PTPA) values—2.5 mm (low), 3.5 mm (medium), and 5.08 mm (high)—cover a representative range commonly used in industrial applications. The results indicate that variations in the PTPA have an insignificant effect on the Colburn factor, suggesting minimal influence on heat transfer performance. However, the PTPA has a significant effect on the friction factor, with higher PTPA values resulting in increased pressure drops. The fin factor, defined as the ratio between the percentage increase in the convective heat transfer coefficient and the corresponding percentage increase in pressure drop, is used for the investigation. For the air frontal velocities above 2 m/s, the fin factor of the CSF with a PTPA of 2.50 mm is higher than those with PTPA values of 3.50 mm and 5.08 mm. This indicates better overall performance in terms of a heat transfer-to-pressure drop trade-off at lower amplitudes.